Functional substitution of mouse ribosomal protein L27' for yeast ribosomal protein L29 in yeast ribosomes. - Fleming, G (1989)
A cDNA clone of mouse ribosomal protein L27' was shown previously to be 62% identical in amino acid residues to yeast ribosomal protein L29. The L27' cDNA was expressed in yeast to determine the ability of the mouse protein to substitute for yeast L29 in assembling a functional ribosome. In a yeast strain resistant to cycloheximide by virtue of a recessive mutation in the L29 protein, the murine cDNA did not produce a sensitive phenotype, indicating failure of the mouse L27' protein to assemble into yeast ribosomes. However, when the mouse L27' gene was expressed in cells devoid of L29 and otherwise inviable, the murine protein supported normal growth, demonstrating that mouse ribosomal protein L27' indeed was interchangeable with yeast L29. We conclude that mouse ribosomal protein L27' is assembled into ribosomes in yeast, but yeast L29 is assembled preferentially when both L29 and L27' are present in the same cell.